Capparis spinosa L. aqueous extract evokes antidiabetic effect in streptozotocin-induced diabetic mice - Mohamed Eddouks; Ahmed Lemhadri; Morad Hebi; Ahmed EL Hidani; Naoufel Ali Zeggwagh; Bachir EL Bouhali; Lhoussaine Hajji; Remy Burcelin (Avicenna Journal of Phytomedicine, 2017)
Objective: As the aqueous extract of Capparis spinosa (CS) possess antidiabetic effect, he present study aims to reveal the possible  mechanism of action of CS in diabetic mice.Materials and Methods: Both single and repeated oral administrations of aqueous extract of CS were performed in multi-low dose streptozotocin-induced (MLDS) diabetic mice. Euglycemic hyperinsulinemic clamp was used in association with the endogenous glucose production (perfusion rate of 3-3H glucose) to evaluate the effect of CS aqueous extract on insulin sensitivity.Results: Our study showed that aqueous extract of CS possess a potent hypoglycaemic activity in MLDS diabetic mice. Furthermore, the analysis perfusion of 3-3H glucose demonstrated  the parallel decrease of basal endogenous glucose production (EGP) with the hypoglycaemic activity. EGP was lower in CS-Treated group when compared to the control group (p